2017
DOI: 10.1292/jvms.17-0052
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A virus infection in Japanese wild boars (<i>Sus scrofa leucomystax</i>)

Abstract: Serum samples were collected from 385 wild boars between 2010 and 2013 to examine the seroprevalence of influenza A virus (IAV) in Japan. Antibodies against IAV were identified using a commercial kit in 13 wild boars (3.4%). To identify the serotypes, positive sera were examined by virus-neutralization test using representative serotypes and strains. Three wild boars in Yamaguchi and four in Tochigi showed the highest antibody titers against the pandemic H1N1 2009 virus and classical swine H1N1 virus strains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Virus‐neutralization tests demonstrated that IAVs whose HA and NA are antigenically closely related to the H1N1pdm09 virus were predominantly distributed in Japanese wild boar populations in Kagoshima prefecture, Japan. After the spread of the H1N1pdm09 virus and their reassortant strains in human and domestic pig populations worldwide, the percentage of wild boars seropositive against pandemic‐related strains was found to be much higher than those against other subtypes of IAVs . Several studies have shown that multiple subtypes of IAVs infections, including H1N1, H1N2, and H3N2, have been diagnosed in wild boars .…”
Section: Summary Of the Results Of Serological Test Using Virus‐neutrmentioning
confidence: 99%
See 3 more Smart Citations
“…Virus‐neutralization tests demonstrated that IAVs whose HA and NA are antigenically closely related to the H1N1pdm09 virus were predominantly distributed in Japanese wild boar populations in Kagoshima prefecture, Japan. After the spread of the H1N1pdm09 virus and their reassortant strains in human and domestic pig populations worldwide, the percentage of wild boars seropositive against pandemic‐related strains was found to be much higher than those against other subtypes of IAVs . Several studies have shown that multiple subtypes of IAVs infections, including H1N1, H1N2, and H3N2, have been diagnosed in wild boars .…”
Section: Summary Of the Results Of Serological Test Using Virus‐neutrmentioning
confidence: 99%
“…Furthermore, cutoff values have been determined using experimental results from sera that had relatively high antibody titers, associated with immune responses from recent infection or immunization . Among commercial ELISA kits that detect IAV infections, the IDEXX Influenza A Ab test seems to work well for surveillance in wild boars . However, the appropriate cutoff value has yet to be determined when the test is applied to wild boar sera.…”
Section: Summary Of the Results Of Serological Test Using Virus‐neutrmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirmed infection is notifiable to OIE. Consistent with this concern is the identification in wild suids of both avian and human influenza virus infections including pandemic H1N1 2009, classical H1N1, H1N2, H3N2 (Biondo et al, 2014;Cano-Manuel et al, 2014;Cho et al, 2015;Foni et al, 2013;Kaden et al, 2008;Perera et al, 2013;Shimoda et al, 2017;Touloudi et al, 2015;Vicente et al, 2002). In one study, H1N2 virus was associated with bronchopneumonia in boars; however, it is unknown if the virus was contributory, as IHC was negative for influenza A and positive for Mycoplasma hyopneumoniae (Biondo et al, 2014).…”
Section: Rna Virusesmentioning
confidence: 96%